2021
DOI: 10.1080/13102818.2021.1901609
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the CCCH gene family in rose (Rosa chinensis Jacq.) reveals its potential functions

Abstract: View related articlesView Crossmark dataGenome-wide identification of the CCCH gene family in rose (Rosa chinensis Jacq.) reveals its potential functions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…These proteins are rather unusual in that they can regulate the expression of genes by binding to mRNA in addition to DNA ( Kim et al., 2014 ; Qin et al., 2014 ). Functional analyses of CCCH genes in Arabidopsis , rice, maize, poplar, alfalfa ( Medicago truncatula ), citrus, tomato, banana, cabbage, soybean, rose, tobacco, and other plants have been conducted ( Wang et al., 2008 ; Chai et al., 2012 ; Peng et al., 2012 ; Zhang et al., 2013 ; Liu et al., 2014 ; Xu, 2014 ; Mazumdar et al., 2017 ; Pi et al., 2018 ; Hu and Zuo, 2021 ; Li et al., 2021 ; Tang C. et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins are rather unusual in that they can regulate the expression of genes by binding to mRNA in addition to DNA ( Kim et al., 2014 ; Qin et al., 2014 ). Functional analyses of CCCH genes in Arabidopsis , rice, maize, poplar, alfalfa ( Medicago truncatula ), citrus, tomato, banana, cabbage, soybean, rose, tobacco, and other plants have been conducted ( Wang et al., 2008 ; Chai et al., 2012 ; Peng et al., 2012 ; Zhang et al., 2013 ; Liu et al., 2014 ; Xu, 2014 ; Mazumdar et al., 2017 ; Pi et al., 2018 ; Hu and Zuo, 2021 ; Li et al., 2021 ; Tang C. et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of CCCH genes in pepper varied significantly among tissues and developmental stages ( Chai et al., 2012 ; Li et al., 2021 ). Only the expression of PEPTY24, PEPTY29 , and PEPTY54 was up-regulated in flowers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified and characterized 50 C3H genes from the potato genome, which were similar to those identified in other Solanaceae species, Solanum lycopersicum (47 members) and Capsicum annuum (57 members) [ 47 , 53 ]. The number of C3H genes varies among plant species, for example, rose (31 members) and Medicago truncatula (34 members) have fewer C3H members, and the number of C3H genes in Brassica rapa (103 members) and Glycine max (116 members) are significantly higher than those in other species [ 47 , 52 , 54 , 55 , 56 ]. Gene duplication is essential for the adaptation and evolution of organisms, and segmental and tandem duplications are considered to play important roles in the expansion of plant gene families [ 57 ].…”
Section: Discussionmentioning
confidence: 99%